A COMPARISON BETWEEN PRONA AND PTSL ON LAND REGISTRATION IN MALANG - Aditya Michael Dinan (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2023)
PRONA and PTSL are policies that aim to accelerate the implementation of land registration in Indonesia. The purpose of this paper is to find out about implementation of land registration through PRONA and PTSL in Malang City. This research uses empirical legal research methods with comparative legal approach analyzed descriptively qualitatively. This study show PRONA activities in 2018 were carried out well (100%). Prona's obstacles consist of many people asking for illegal levies, Pokmasdartibna's lack of scrupulousnes, and participant withdrew due to tax increases. Meanwhile, the results of PTSL activities as of September 22, 2021 were able to reach 90.4% (6,882 SHAT) with inhibiting factors consisting of the lack of human resources of the PTSL implementation committee, insufficient community enthusiasm related to tax payments, the existence of ID cards that have not been validated, many communities incomplete in filling administrative requirements, and uncooperative villagers.